Anaerobic sport-specific tests for taekwondo: a narrative review with guidelines for the assessment - Apollaro, G.; Ouergui, I.; Quiñones Rodríguez, Y.; Kons, R. L.; Detanico, D.; Franchini, E.; Ruggeri, P.; Falcó, C.; Faelli, E. (Sports, 2024)
The ATP-PCr system represents the main source of energy during high-intensity attack actions in taekwondo matches. In contrast, the glycolytic system supports the maintenance of these actions when repeated techniques are performed. Given the close relationship between anaerobic energy systems and attack activity in combat, the literature relating to the use of sport-specific test protocols for anaerobic assessment has experienced a remarkable increase. This narrative review aims to illustrate the sport-specific anaerobic tests available in taekwondo by retracing and examining development and validation process for each test. Forty-one articles published between 2014 and 2023 were selected via the MEDLINE and Google Scholar bibliographic databases. These tests are the Taekwondo Anaerobic Test and Adapted Anaerobic Kick Test (i.e., continuous mode testing); the 10 s and multiple Frequency Speed of Kick Tests; the chest and head Taekwondo Anaerobic Intermittent Kick Tests; and the Taekwondo-Specific Aerobic-Anaerobic-Agility test (i.e., intermittent mode testing). Coaches and strength and conditioning professionals can use all the tests described in taekwondo gyms as they feature short and easy-to-implement protocols for monitoring and prescribing specific anaerobic training. The guidelines in this review evaluate each test from several perspectives: basic (e.g., validity, reliability, and sensitivity), methodological (e.g., continuous or intermittent mode testing) and application (e.g., time-motion structure and performance parameters). This comprehensive approach aims to assist stakeholders in selecting the most appropriate test.